Evaluating the Proposed Mechanism by Which Atorvastatin Can Protect Renal Tissue against Contrast Media: An Animal study - Samer Jaffar Sharif; Bahir Abdul Razzaq Mshimesh; Ahmed Fakhir Hameed; Suzan Suzan Suzan (College of Pharmacy / Mustansiriyah University, 2019)
Contrast- induced nephropathy (CIN) is an elevation of serum creatinine of ≥ 0.5 mg/dL from baseline after two to three days of exposure to contrast substance if there is no other cause for acute kidney injury. Atorvastatin may protect normal kidney physiology from contrast- induced kidney injury by effects unrelated to hypolipidemia termed pleiotropic effect by decline of endothelin production, angiotensin system down regulation, and under expression of endothelial adhesion molecules. This study was conducted to assess the strategy by which atorvastatin can achieve protective effect for kidneys after exposure to contrast media in an animal model. A 40 male rats were distributed randomly into 4 groups; ten rats for each: group (1): given normal saline; group (2): CIN group given iopromide as contrast media; group (3): given atorvastatin (20mg/kg) and iopromide; and group (4): given atorvastatin (40mg/kg) and iopromide. Blood collected by cardiac puncture for detection of serum glutathione, malondialdehyde, matrix metalloproteinase-9, and interleukin-18. The results have shown a significant increase in inflammatory and oxidative stress markers in contrast media group, and significant reduction in these markers in atorvastatin treated groups, in a dose-dependent manner. As conclusion, atorvastatin mechanism for protection against CIN in a dose-dependent manner can mediate by anti-inflammatory and antioxidant effects.